Kecerdasan Emosi Pada Mahasiswa Psikologi Univertas Malikussaleh - Risna Delvina (Jurnal Psikologi Terapan, 2018)
Emotional intelligence is the ability to understand oneself, to empathize with the feelings of others and to regulate the emotions simultaneously in improving one's life. Emotions are circumstances that show people to live and also to manage emotionally needed intelligence. This study aims to see how high the emotional intelligence of Unimal psychology students also in order to establish a scale of intelligence is valid, reliable, and have good aitem. A total of 73 respondents, consisting of 6 men (8.2%), and 67 women (91.78%). The age range of respondents is 17-25 years old. Based on the result of this experiment, it is known that the reliability of emotional intelligence using Alpha Cronbach's technique is α = 0,389 aitem is not reliable because alpha value less than 5 (five). This scale is unreliable, in other words the results of the emotional intelligence measurement experiment can not measure one of the same constructs. The result of correlation between total aitem whose value is below 0.23 is eliminated because it has passed the minimum value of reliable aitem. Thus, the failure of this scale is not good, then the scale of this intelligence can not be used to measure emotional intelligence in the context of research and psychological intervention.